EFFECT OF ECONOMIC GROWTH AND HUMAN DEVELOPMENT INDEX (IPM) ON UNEMPLOYMENT IN INDONESIA - Nita Sanitra (SEAN Institute, 2021)
Unemployment is the most crucial problem in an economy, the problem of unemployment occurs as a result of an imbalance between available employment and the number of workers who increase every year. This research was conducted to find out how much influence economic growth and the human development index have on unemployment in Indonesia for the period 2011-2018. This research is a quantitative research that uses secondary data in the form of panel data. Secondary data was obtained from the Central Statistics Agency. The analytical method used is multiple linear regression analysis with the selected model, namely the fixed effect model. The results show that economic growth has a positive and insignificant effect on unemployment in Indonesia. While the human development index has a negative and significant effect on unemployment in Indonesia. The suggestion from this research is that the government should pay more attention to the HDI sector by increasing and distributing it to remote areas where the HDI level is still lacking or low.